Utilization of Industrial Byproducts for Enhancing the Properties of Cement Mortars at Elevated Temperatures - Vasiliki Pachta (MDPI AG, 2021)
The research on industrial byproducts, such as slags and fly ash, was intense during the last decades in the building sector. Apart from the environmental benefits coming from their exploitation, their application may lead to the production of cost effective and durable building materials, such as mortars and concrete. The impact of industrial byproducts on the resistance of materials to fire and elevated temperatures was assessed by many scientists, however, it is still an open field of research. In this study, locally available byproducts were investigated, including High Calcium Fly Ash (HCFA), coming from lignite-fired power plants, as well as Ladle Furnace Steel (LFS) slag and Electric Arc Furnace (EAF) slag aggregates, originating from the steel making industry. Six mortar compositions were manufactured with substitution of Ordinary Portland Cement (OPC) with HCFA and LFS slag (20% w/w) and of natural aggregates with EAF slag (50% w/w). At the age of 7, 28, and 90 days, the physico-mechanical properties of the specimens were recorded, while they were further exposed at elevated temperatures, concerning 200 °C, 400 °C, 600 °C, 800 °C, and 1000 °C. After each exposure, their physico-mechanical and microstructure characteristics were identified. From the evaluation of the results, it was asserted that HCFA and EAF slag aggregates enhanced the overall performance of mortars, especially up to 600 °C. LFS was beneficial only in combination with EAF slag aggregates.